PENGARUH FINANCIAL SELF EFFICACY DAN SOCIAL MEDIA INFLUENCER TERHADAP NIAT INVESTASI EMAS DIMODERASI INVESTMENT KNOWLEDGE - Nelista Rizkiyati; Muhadjir Anwar; G. Oka Warmana (STKIP Persada Khatulistiwa Sintang, 2025)
Gold investment in ANTAM precious metals is considered a safe and profitable long-term investment option. In the digital era, various psychological and social factors such as financial self-efficacy and Social Media Influencer play a key role in shaping individuals’ investment intentions. This study aims to examine the effect of financial self-efficacy and Social Media Influencers on investment intention in ANTAM gold, with Investment Knowledge as a moderating variable. A quantitative method was used, employing a Likert scale to measure the research variables. Convenience sampling was applied with a total of 190 respondents participating in the study. Data analysis and hypothesis testing were conducted using Partial Least Squares (PLS) via SmartPLS software. The results show that both financial self-efficacy and Social Media Influencers have a positive and significant effect on investment intention. Furthermore, Investment Knowledge significantly moderates the relationship between financial self-efficacy and investment intention, but does not moderate the effect of Social Media Influencers.